Facing disadvantages: The changing professional identities of college English teachers in a managerial context. (June 2019) - Huang, Ya-Ting; Guo, Ming
Abstract: Despite the significant role of managerial technologies in influencing university faculty members' academic lives, little is known about how the professional identities of Chinese college English teachers have undergone a dynamic process of formation, negotiation, and/or renegotiation under the influence of managerialism of higher education. Drawing on the socio-cultural perspective of professional identity, this study adopted a longitudinal qualitative approach that followed three college English teachers over four years, and included four waves of data collection. The findings mapped the cognitive, emotional, and behavioural developments of the participants' professional identities over the course of those four years, illustrating the complexity of identity negotiation, through which teachers must reconcile new expectations and conflicting demands. This study offers practical implications to facilitate college English teachers' adaption to their new environment.